2010
DOI: 10.1080/00071668.2010.495746
|View full text |Cite
|
Sign up to set email alerts
|

Brooding temperatures for chicks acclimated to heat during incubation: effects on post-hatch intestinal development and body weight under heat stress

Abstract: 1. The objective was to evaluate the effects of brooding temperature on intestinal development, oxidative organ damage, and performance of chicks acclimated to high temperature during incubation. The effects of acclimation and brooding temperatures on slaughter weights of broilers under heat stress were also investigated. 2. Eggs were incubated at either 378 degrees C (INC(Cont)) or heat-acclimated at 395 degrees C for 6 h daily from d 10 to d 18 of incubation (INC(H)). Brooding temperatures at floor level wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
1
9
0
2
Order By: Relevance
“…This result was consistent with the results of both long-term hightemperature, environment-treated studies (Piestun et al, 2008;Akşit et al, 2010;Yalçin et al, 2010) and short-term high-temperature, environment-treated studies (Moraes et al, 2004;Yahav et al, 2004a and2004b;Collin et al, 2007). By contrast, there are few studies suggesting that the high temperature applied during incubation has an effect on the hatching weight in broilers.…”
Section: Discussionsupporting
confidence: 89%
“…This result was consistent with the results of both long-term hightemperature, environment-treated studies (Piestun et al, 2008;Akşit et al, 2010;Yalçin et al, 2010) and short-term high-temperature, environment-treated studies (Moraes et al, 2004;Yahav et al, 2004a and2004b;Collin et al, 2007). By contrast, there are few studies suggesting that the high temperature applied during incubation has an effect on the hatching weight in broilers.…”
Section: Discussionsupporting
confidence: 89%
“…The exposure of eggs to high temperatures (38.50ºC) for 4-6 hours between the 10 th and 16 th days of incubation may improve the capacity to adapt to heat stress in the fifth week (AKSIT et al, 2010). YALÇIN et al (2010) reported better adaptation to high temperatures in broilers between the third and sixth post-hatching weeks, minimizing the negative effects caused by heat stress on slaughter weight and breast yield after exposure to temperatures of 39.60ºC for 6h from the tenth to the eighteenth days of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…This depressed feed intake would decrease bodily heat production and could help to minimize heat stress. In addition Aksit et al (2010) observed that when eggs were heat acclimatised (incubated at 39.5°C for 6 h daily from d 10 to d 18) and these chicks were kept at a high brooding temperature of 35°C they had lower H:L ratios than 'control' chicks incubated at 37.5°C. Lower H:L ratios also suggest that heat acclimatised birds may cope better with heat stress.…”
Section: Broodingmentioning
confidence: 99%